Manual versus rotary instrumentation for primary molar pulpectomies- A 24 months randomized clinical trial. Issue 2 (August 2018) - Morankar, R.; Goyal, A.; Gauba, K.; Kapur, A.; Bhatia, S.K.
Abstract: Objective: The study compared manual and rotary canal instrumentation differences in primary molars receiving pulpectomy and their effect on clinical success after two years. Materials and methods: Sixty pulpally involved primary mandibular second molars requiring pulpectomy treatment were randomly assigned for manual or rotary instrumentation in children aged 4–7 years. The endodontic procedural steps were similar except the method of root canal instrumentation i.e. manual group (Stainless steel files 2% taper) and rotary group (Hyflex CM NiTi rotary files 4% taper). Results: The mean instrumentation time for the manual and rotary groups were 25.71 ± 3.84 and 19.37 ± 4.94 min respectively with a statistically significant difference (p < 0.001) between the groups. The differences between the groups' obturation time, quality of obturation, and complications during instrumentation were not statistically significant (p > 0.05). At 24 months, the clinical success was 92.3% and 85.2% (p = 0.52) whereas the radiographic success was 65.4% and 66.7% (p = 0.78) comparing the manual and rotary groups respectively. Conclusion: Rotary instrumentation takes significantly less time than manual. There was no difference in obturation time, quality of obturation, or success rates after 24 months.